Alone together: Biographical crises in times of pandemix - Caetano, A. (European Sociologist, 2021)
I have been studying biographical crises for some years now. My interest is in understanding how people cope with very personal difficult moments experienced over the course of their lives. I am examining critical events and periods connected, for example, to the death of someone close, a disease, accidents, severe economic difficulties, among other traumatic occurrences [1]. One of the main features of this type of micro analysis is that it examines extremely private dimensions of a person’s life, and deals with the exceptionality and sometimes even unpredictability of these events in that person’s biography. It is true that many of these crises illustrate the individual dimension of larger societal trends. An accident, a death, or a disease can be understood at the individual level as the result of chance, but if we look at the global picture, these are events that are quite common in people’s biographies. They are individually unexpected but collectively probable. And while they tend to have disruptive effects, there are institutional responses to such circumstances [2]. Societies are prepared, through their institutions, to deal with these negative moments, precisely because they are integral parts of social life.